Simultaneous determination of pioglitazone and candesartan in human plasma by LC-MS/MS and its application to a human pharmacokinetic study - Vijaya Kumari Karra; Nageswara Rao Pilli; Jaswanth Kumar Inamadugu; J.V.L.N. Seshagiri Rao (Elsevier, 2012)
A simple and rapid liquid chromatography-tandem mass spectrometric (LC-MS/MS) assay method has been developed and fully validated for simultaneous quantification of pioglitazone and candesartan in human plasma. Irbesartan was used as an internal standard. The analytes were extracted from human plasma samples by solid-phase extraction technique using a Strata-X 33Â Î¼m polymeric sorbent. The reconstituted samples were chromatographed on a C18 column by using a 80:20 (v/v) mixture of acetonitrile and 0.1% formic acid as the mobile phase at a flow rate of 0.8Â mL/min. The calibration curves obtained were linear (râ¥0.99) over the concentration range of 15â3000Â ng/mL for pioglitazone and 5â608Â ng/mL for candesartan. The results of the intra- and inter-day precision and accuracy studies were well within the acceptable limits. A run time of 2.7Â min for each sample made it possible to analyze more than 300 plasma samples per day. The proposed method was found to be applicable to clinical studies. Keywords: Pioglitazone, Candesartan, Human plasma, Solid-phase extraction, LC-MS/MS, Pharmacokinetics